FISCAL POLICY AND LONG-TERM ECONOMIC GROWTH: LESSONS FROM THE EURO AREA - Ferreiro, Jesus; Gomez, Carmen Elena (Práticas de Administração Pública, 2022)
At the beginning of 2020, the European Union embarked on a process of reviewing its macroeconomic policy strategy and economic governance framework. While the review of the monetary policy framework was approved in July 2021, the review of the fiscal policy framework was put on hold as a result of the outbreak of the covid-19 pandemic and the ensuing economic crisis. The Covid-19 crisis led to a breach of fiscal rules in the European Union and an unprecedented increase in the size of fiscal imbalances. In this context, there is a need for a radical reform of the fiscal rules still in force to allow for a more active role of national fiscal policies and to avoid the serious economic problems resulting from the fiscal austerity policies emanating from the Maastricht Treaty, the Stability and Growth Pact and the successive reforms of the latter.